2015
DOI: 10.1002/mnfr.201500422
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia‐induced hepatic and small intestine ER stress and decreased paraoxonase 1 expression and activity is associated with HDL dysfunction in Syrian hamsters

Abstract: The fat diet activates the ERS and oxidative stress, decreases LXRβ, PPARγ, and PON1 in the small intestine, liver, and sera of all HL animals, in parallel with the appearance of atherosclerotic lesions in the aortic valves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…This could be due to the different animal models and methods for ginger extract preparation that were used . Our group has previously shown that a high‐fat diet induces the decrease of PPARγ protein expression in the SI . The here reported results evidence for the first time that GIN increases PPARγ gene and protein expression in the SI, a possible explanation for the observed increase of apoA‐I levels.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…This could be due to the different animal models and methods for ginger extract preparation that were used . Our group has previously shown that a high‐fat diet induces the decrease of PPARγ protein expression in the SI . The here reported results evidence for the first time that GIN increases PPARγ gene and protein expression in the SI, a possible explanation for the observed increase of apoA‐I levels.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, plasma MPO/PON1 ratio was suggested as a potential predictor of dysfunctional HDL and an indicator of risk stratification in coronary artery disease patients . We have previously reported that HL causes the decrease of apoA‐I protein in the SI . The novelty of our present results resides in evidencing that HL generates oxidized‐apoA‐I in the SI and that this process is associated with the increase of MPO and the decrease of PON1 protein levels in the tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paraoxonase 1 (PON1) is an antioxidant enzyme physically associated with HDL particles, its activity being dependent on the levels of apoAI, apoAII and myeloperoxidase (MPO) in HDL 6 , 7 . PON1 is a Ca 2+ -dependent serum esterase that is synthesized mainly in the liver, but also in the intestine and kidney 14 16 . The enzyme has aryl esterase, paraoxonase and lactonase activities, being able to degrade oxidized phospholipids and hydrolyze lactones from lipoproteins and cells 14 .…”
Section: Introductionmentioning
confidence: 99%